Correcting misperceptions of the other political party does not robustly reduce support for undemocratic practices or partisan violence - Druckman, James N. (Proceedings of the National Academy of Sciences - PNAS, 2023)
A growing consensus suggests that a cause of support for undemocratic practices and partisan violence is that partisans misperceive the other side. That is, they vastly exaggerate the extent to which members of the other party support undemocratic practices and violence. When these misperceptions are corrected, citizens’ own beliefs moderate. I present results from an experiment that show that misperception corrections do not have an effect in the presence of competing information (i.e., that challenges the validity of the correction or offers a conflicting narrative). Basic corrections do not constitute a robust way to counter democratic backsliding stemming from citizens’ misperceptions. The results highlight the need to devise stronger misperception interventions and, more generally, to consider competing information environments when devising any scalable behavioral intervention.